Mortality outcomes in 35,433 patients admitted for acute haemorrhagic stroke in Australia: A population-linkage study - Arielle Chin-yu Hsu; Vijayatubini Vijayarajan; Yeu-Yao Cheng; Matthew Wei Shun Shu; Karice Hyun; Vincent Chow; David Brieger; Leonard Kritharides; Austin Chin Chwan Ng (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2024)
Background: Haemorrhagic stroke (HS) is an important cardiovascular cause of mortality worldwide. Trends in admission rates and outcomes, and predictors of outcomes, post-HS in Australia remain unclear. Methods: All New South Wales residents, Australia, hospitalized with HS from 2002 to 2017 were identified from the Admitted-Patient-Data-Collection database. Admission rates were adjusted to population size by sex, age-groups and calendar-year. Mortality was tracked from the death registry to 31-Dec-2018 and adjusted for admission calendar-year, age, gender, referral source, surgical evacuation following HS and comorbidities. Results: The cohort comprised 35,433 patients (51.1% males). Overall age-adjusted mean(±SD) admission rates were higher for males (63.6 ± 6.2 vs 49.9 ± 4.4 admissions-per-100,000-persons-per-annum). Annual admission rates declined for both sexes from 2002 to 2017 especially in those ≥60yo. In-hospital and 1-year mortality rates were higher for females than males (25.0% vs 20.0% and 40.6% vs 35.9% respectively, all p < 0.001). Adjusted in-hospital and 1-year mortality declined for men and women, overall decreasing by 45% (odds ratio 0.55, 95% confidence interval [CI] = 0.47–0.64), and 31% (hazard ratio 0.69,95%CI = 0.63–0.76) respectively between 2002 and 2017. Independent predictors of increased in-hospital and 1-year mortality included increasing age and Charlson comorbidity index, while male sex, a history of hyperlipidaemia and current smoking, and surgical evacuation following HS were associated with reduced mortality (all p < 0.001). Conclusion: HS incidence increases markedly with age. Although age-adjusted HS admission rates and post HS mortality have fallen, HS remains associated with high early and 1-year mortality, with females consistently associated with worse outcomes. Strategies to improve outcomes of these patients remain a clinical priority.